Reorientation of the Objectives of Islamic Education in the Modern Era in the Formation of Islamic Personality - Sabrina Khairunnisa Zulkarnain; Syamsul Aripin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Islamic education faces significant transformation challenges in the modern era due to globalization and technological advancements that shift orientation from holistic personality formation toward academic pragmatism. This literature study aims to analyze ideal Islamic education goals, identify modern-era shifting problems, and propose reorientation solutions. Using qualitative approach through analysis of scientific journals and recent publications (2017-2025), findings are grouped into conceptual goals, modernization realities, orientation shifts, and reorientation strategies. Results show reorientation requires interdisciplinary curriculum integrating Islamic values with contemporary pedagogical innovations like participatory learning, strengthening teacher role as murabbi, and institutional culture transformation. Main outcomes provide practical recommendations for Islamic institutions to produce graduates professionally competent while maintaining strong Islamic character, contributing to rahmatan lil alamin society development.